SMART SPECIALISATIONS IN REGIONAL INNOVATION ECOSYSTEM - Pyka, Jan; Janiszewski, Adam (Journal of European Economy, 2017)
In times of economic crisis creating new kinds of advantages remains a key task which determines a quick recovery from economic difficulties as well as whether the fast socio – economic development of the country is achieved. These advantages should be based on the use of knowledge, intellectual capital and abilities of the state and local self governments’ structures to support and establish conditions for the innovative development of the country and its regions.RIS is a public policy instrument whose guidelines are directed at a priority of the innovative development. The paper presents both the methodical foundation for building the regional innovation strategy and vision for the development of an in novation ecosystem in Region.